2023
DOI: 10.1038/s42003-023-04475-0
|View full text |Cite
|
Sign up to set email alerts
|

The antidiabetic drug metformin aids bacteria in hijacking vitamin B12 from the environment through RcdA

Abstract: Years of use of the antidiabetic drug metformin has long been associated with the risk of vitamin B12 (B12) deficiency in type 2 diabetes (T2D) patients, although the underlying mechanisms are unclear. Accumulating evidence has shown that metformin may exert beneficial effects by altering the metabolism of the gut microbiota, but whether it induces human B12 deficiency via modulation of bacterial activity remains poorly understood. Here, we show that both metformin and the other biguanide drug phenformin marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Further, treatment with metformin, currently the first-line treatment of T2DM, has been shown to cause vitamin B12 deficiency [ 241 ]. A recent study showed that metformin can assist gut microbiota in contributing to this deficiency [ 242 ]. Using functional and genomic analyses via high-throughput screens for E. coli and C. elegans, it was shown that metformin helps bacteria gather B12 from the environment by increasing the expressions of B12 transporter genes, thus reducing the B12 supply to T2D patients taking the drug over time [ 242 ].…”
Section: Effects Of Micronutrients On T2dm and Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Further, treatment with metformin, currently the first-line treatment of T2DM, has been shown to cause vitamin B12 deficiency [ 241 ]. A recent study showed that metformin can assist gut microbiota in contributing to this deficiency [ 242 ]. Using functional and genomic analyses via high-throughput screens for E. coli and C. elegans, it was shown that metformin helps bacteria gather B12 from the environment by increasing the expressions of B12 transporter genes, thus reducing the B12 supply to T2D patients taking the drug over time [ 242 ].…”
Section: Effects Of Micronutrients On T2dm and Gut Microbiotamentioning
confidence: 99%
“…A recent study showed that metformin can assist gut microbiota in contributing to this deficiency [ 242 ]. Using functional and genomic analyses via high-throughput screens for E. coli and C. elegans, it was shown that metformin helps bacteria gather B12 from the environment by increasing the expressions of B12 transporter genes, thus reducing the B12 supply to T2D patients taking the drug over time [ 242 ]. It is important to note that vitamin B12 deficiency can further exacerbate the sequelae of T2DM such as peripheral neuropathy and even macrovascular complications in patients with the condition [ 243 ].…”
Section: Effects Of Micronutrients On T2dm and Gut Microbiotamentioning
confidence: 99%
“…Further, treatment with metformin, currently the first-line treatment of T2DM, has been shown to cause vitamin B12 deficiency [241]. Recent study showed that metformin can assist gut microbiota in contributing to this deficiency [242]. Using functional and genomic analyses via high-throughput screens in E. coli and C. elegans it was shown that metformin helps bacteria gather B12 from the environment by increasing the expressions of B12 transporter genes thus reducing the B12 supply to T2D patients taking the drug over time [242].…”
Section: Vitamins Gut Microbiota and T2dmmentioning
confidence: 99%
“…Recent study showed that metformin can assist gut microbiota in contributing to this deficiency [242]. Using functional and genomic analyses via high-throughput screens in E. coli and C. elegans it was shown that metformin helps bacteria gather B12 from the environment by increasing the expressions of B12 transporter genes thus reducing the B12 supply to T2D patients taking the drug over time [242]. It is important to note that Vitamin B12 deficiency can further exacerbate sequelae of T2DM such as peripheral neuropathy and even macrovascular complications in patients with the condition [243].…”
Section: Vitamins Gut Microbiota and T2dmmentioning
confidence: 99%
“…Hyperhomocysteinemia and dementia are associated with VitB12 de ciency [12] . The potential reasons for VitB12 de ciency include malnutrition; malabsorption; genetic changes in the way that VitB12 is transported in the blood, cellular uptake, or metabolic route [13] ; autoimmune diseases or pernicious anemia [9] ; and some medications such as proton pump inhibitors [14] and metformin [15] .…”
Section: Introductionmentioning
confidence: 99%